Cellular Accumulation and Activity of Quinolones in Ciprofloxacin-Resistant J774 Macrophages - Michot, Jean-Michel (American Society for Microbiology, 2006)
Ciprofloxacin is the substrate for a multidrug resistance-related protein (MRP)-like multidrug transporter in J774 mouse macrophages, which also modestly affects levofloxacin but only marginally affects garenoxacin and moxifloxacin (J.-M. Michot et al., Antimicrob. Agents Chemother. 49:2429-2437, 2005). Two clones of ciprofloxacin-resistant cells were obtained by a stepwise increase in drug concentration (from 34 to 51 to 68 mg/liter) in the culture fluid. Compared to wild-type cells, ciprofloxacin-resistant cells showed (i) a markedly reduced ciprofloxacin accumulation (12% of control) and (ii) a two- to threefold lower sensitivity to the enhancing effect exerted by MRP-inhibitors (probenecid and MK571) on ciprofloxacin accumulation or by ciprofloxacin itself. ATP-depletion brought ciprofloxacin accumulation to similarly high levels in both wild-type and ciprofloxacin-resistant cells. Garenoxacin and moxifloxacin accumulation remained unaffected, and levofloxacin showed an intermediate behavior. DNA and protein synthesis were not impaired in ciprofloxacin-resistant cells for ciprofloxacin concentrations up to 100 mg/liter (∼85 and 55% inhibition, respectively, in wild-type cells). In Listeria monocytogenes-infected ciprofloxacin-resistant cells, 12-fold higher extracellular concentrations of ciprofloxacin were needed to show a bacteriostatic effect in comparison with wild-type cells. The data suggest that the resistance mechanism is mediated by an overexpression and/or increased activity of the MRP-like ciprofloxacin transporter expressed at a basal level in wild-type J774 macrophages, which modulates both the intracellular pharmacokinetics and activity of ciprofloxacin.